Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.

PolyHIPE derived freestanding 3D carbon foam for cobalt hydroxide nanorods based highperformance supercapacitor - Patil, Umakant M.; Ghorpade, Ravindra V.; Nam, Min Sik; Nalawade, Archana C.; Lee, Sangrae; Han, Haksoo; Jun, Seong Chan (Scientific Reports, 2016)
The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)(2)) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)(2)/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 degrees C to obtain graphitic 3D carbon foam with high surface area (389 m(2) g(-1)) having open voids (14 mu m) interconnected by windows (4 mu m) in monolithic form. Moreover, entangled Co(OH)(2) NRs are anchored on 3D GCF electrodes by using a facile chemical bath deposition (CBD) method. The wide porous structure with high specific surface area (520 m(2) g(-1)) access offered by the interconnected 3D GCF along with Co(OH)(2) NRs morphology, displays ultrahigh specific capacitance, specific energy and power. The Co(OH)(2)/3D GCF electrode exhibits maximum specific capacitance about similar to 1235 F g(-1) at similar to 1 Ag-1 charge-discharge current density, in 1 M aqueous KOH solution. These results endorse potential applicability of Co(OH)(2)/3D GCF electrode in supercapacitors and signifies that, the porous GCF is a proficient 3D freestanding framework for loading pseudocapacitive nanostructured materials.

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .